2023
DOI: 10.3390/app13085014
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Enabled Project Management: A Systematic Literature Review

Abstract: In the Industry 5.0 era, companies are leveraging the potential of cutting-edge technologies such as artificial intelligence for more efficient and green human-centric production. In a similar approach, project management would benefit from artificial intelligence in order to achieve project goals by improving project performance, and consequently, reaching higher sustainable success. In this context, this paper examines the role of artificial intelligence in emerging project management through a systematic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 145 publications
(158 reference statements)
0
4
0
Order By: Relevance
“…The study shows that, while its application is not yet widespread, AI is used to plan, schedule, and monitor projects. Similarly, in [26], the results demonstrate that ML is highly beneficial for construction PM due to its capacity to enhance planning, measurement, performance, and decision-making. In [27], it is demonstrated that AI has a positive impact on risk management, cost efficiency, and time efficiency.…”
Section: Review Of Relatedmentioning
confidence: 78%
See 1 more Smart Citation
“…The study shows that, while its application is not yet widespread, AI is used to plan, schedule, and monitor projects. Similarly, in [26], the results demonstrate that ML is highly beneficial for construction PM due to its capacity to enhance planning, measurement, performance, and decision-making. In [27], it is demonstrated that AI has a positive impact on risk management, cost efficiency, and time efficiency.…”
Section: Review Of Relatedmentioning
confidence: 78%
“…This study identifies the most commonly used AI techniques to enhance PM in construction. In [26], ML is presented as a powerful tool in AI that relies on classifying and predicting information. It utilizes a range of architectures and algorithms to learn from the input data, ultimately resulting in the creation and training of a model capable of making predictions based on the analyzed and learned information.…”
Section: Rq2: What Are the Most Commonly Used Ai Techniques And/or Al...mentioning
confidence: 99%
“…al. [40] looks at how artificial intelligence (AI) is being used in project management to make projects run better. It studies how AI can help with making decisions and getting better results overall.…”
Section: Related Workmentioning
confidence: 99%
“…Artificial intelligence models can pick up prejudices from the information they are trained with, which can result in unfair or discriminatory results. It is very important to address unfairness and inequality in AI systems Taboada [40]. Using AI and Big Data solutions can be difficult and need a lot of resources.…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…AI and ML in Construction 5.0 improve predictive maintenance and adaptive control. Intelligent algorithms that examine large data sets to make judgments are a promising research field [123]. Multi-Access Edge Computing (MEC) technology extends cloud computing to wireless access networks near end-users.…”
Section: Sustainable Development In the Aec Industry Areamentioning
confidence: 99%